Between Illusion and Reality: Jia Zhangke's Vision of Present-day China in The World. Issue 2 (1st September 2007) - Shi, Xiaoling
After filming a series of young and insignificant flaneurs strolling at the margin of cities, in The World, Jia Zhangke's attention has focused on migrant workers, who seem to be the only subaltern that the mainstream discourse can tolerate. Among all the films Jia has so far directed, The World is the only one that has passed the censorship of the Chinese government and has been allowed to be presented to the public. However, like his censored films, The World connotes Jia's consistent derision of contemporary Chinese politics. Perhaps the censors are elated by both the panoply shown on the stage of the World Park and the multicolored animation displayed on the screen, the brightness of which cannot be seen in Jia's previous films. Yet, by juxtaposing the gay festivity of the park with the gloomy real life of migrant workers, Jia acutely expresses a dismal view of present-day China: the Chinese think they are living in a modern society and believe that China has become a significant part of the international community; it is, however, just an illusion. Perhaps, more deplorably, in the course of chasing after the West, the Chinese have lost sense of their culture.